Parkinson's disease–associated mutant VPS35 causes mitochondrial dysfunction by recycling DLP1 complexes - Wang, Wenzhang; Wang, Xinglong; Fujioka, Hisashi; Hoppel, Charles; Whone, Alan L; Caldwell, Maeve A; Cullen, Peter J; Liu, Jun; Zhu, Xiongwei (Nature medicine, 2016)
Mutations in VPS35 that are associated with Parkinson's disease increase the interaction of VPS35 with mitochondrial DLP1, leading to removal of the DLP1 complexes and mitochondrial fragmentation. Structural and functional mitochondrial impairments caused by mutant VPS35 are observed in vitro using cultured neurons and fibroblasts from individuals with PD and in vivo in mouse substantia nigra neurons, where they induce neurodegeneration. Mitochondrial dysfunction represents a critical step during the pathogenesis of Parkinson's disease (PD), and increasing evidence suggests abnormal mitochondrial dynamics and quality control as important underlying mechanisms. The VPS35 gene, which encodes a key component of the membrane protein–recycling retromer complex, is the third autosomal-dominant gene associated with PD. However, how VPS35 mutations lead to neurodegeneration remains unclear. Here we demonstrate that PD-associated VPS35 mutations caused mitochondrial fragmentation and cell death in cultured neurons in vitro, in mouse substantia nigra neurons in vivo and in human fibroblasts from an individual with PD who has the VPS35 D620N mutation. VPS35 -induced mitochondrial deficits and neuronal dysfunction could be prevented by inhibition of mitochondrial fission. VPS35 mutants showed increased interaction with dynamin-like protein (DLP) 1, which enhanced turnover of the mitochondrial DLP1 complexes via the mitochondria-derived vesicle–dependent trafficking of the complexes to lysosomes for degradation. Notably, oxidative stress increased the VPS35-DLP1 interaction, which we also found to be increased in the brains of sporadic PD cases. These results revealed a novel cellular mechanism for the involvement of VPS35 in mitochondrial fission, dysregulation of which is probably involved in the pathogenesis of familial, and possibly sporadic, PD.